A sudden rampage the Japanese occupation of Southeast Asia, 1941-1945 - Tarling, Nicholas (University of Hawai'i Press, 2001)
A Sudden Rampage describes Japan's occupation of Southeast Asia during World War II in the context of its relationship with the outside world. The first two chapters focus on the period between the Meiji restoration, the end of World War I, the interwar period, and the outbreak of war in the Pacific. Subsequent chapters offer a short narrative of the Pacific conflict and a country by country description of Japan's political activities in the occupied region and economic activities undertaken by the Japanese in wartime Southeast Asia. The concluding chapter assesses the contribution the occupation made to postwar Southeast Asia in the light of the suffering and destruction rendered on the region.